Aging Decreases Hand Volume Expansion with Water Immersion - Siamwala, Jamila H.; Moossazadeh, Davina G.; Macaulay, Timothy R.; Becker, Rachel L.; Hargens, Rekha H.; Hargens, Alan R. (Frontiers in Physiology, 2018)
Hands may show early signs of aging with altered skin texture, skin permeability and vascular properties. In clinics, a hand volumeter is used to measure swelling of hands due to edema, carpal tunnel syndrome or drug interventions. The hand volume measurements are generally taken without taking age into consideration. We hypothesized that age affects hand volumeter measurements and that the younger age group (≤40y) records a greater change in hand volume as compared to the older group (>40y). Four volumetric measurements were taken at 5-minute intervals during 20 minutes of water immersion using a clinically-approved hand volumeter. After 20 minutes of immersion, the hand volume changes of the younger age group were significantly higher than the older age group (p<0.001). Specifically, the right-hand volume of the younger age group (≤40y, n=30) increased increases by 4.3±2%, and the left hand increased increases by 3.4±2.1%. Conversely, the right-hand volume of the older age group (>40y, n=10) increased increases by only 2.2±2.0%, and the left hand decreased decreases by 0.6±2.4% after 20min of water immersion. The data are presented as Mean ± SD. Hand volume changes were not correlated with body mass index (BMI) or gender, and furthermore, neither of these two variables affected the relationship between age and hand volume changes with water immersion. We conclude that the younger age group has a higher increase in hand volume with water immersion as compared to the older age group.